2016
DOI: 10.1039/c6ra16311d
|View full text |Cite
|
Sign up to set email alerts
|

Control of SrO buffer-layer formation on Si(001) using the pulsed-laser deposition technique

Abstract: The overview of optimal parameters for deoxidation of the Si(001) surface using SrO and a pulsed-laser deposition method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…A metallic Sr target has been employed for the initial 1/2 ML of Sr passivation of the Si surface. Similarly to growth on Si, it was shown that the understanding and precise control of the structure and reconstructions of this initial Sr Zintl phase, and its evolution, are critical for obtaining STO epitaxy . This critical surface passivation, together with optimized annealing schemes, have significantly promoted higher crystalline qualities, showing considerable progress.…”
Section: Growth Physical and Electronic Structurementioning
confidence: 99%
“…A metallic Sr target has been employed for the initial 1/2 ML of Sr passivation of the Si surface. Similarly to growth on Si, it was shown that the understanding and precise control of the structure and reconstructions of this initial Sr Zintl phase, and its evolution, are critical for obtaining STO epitaxy . This critical surface passivation, together with optimized annealing schemes, have significantly promoted higher crystalline qualities, showing considerable progress.…”
Section: Growth Physical and Electronic Structurementioning
confidence: 99%
“…Besides, the same study reported additional transmission spots the origin of which was not discussed by authors. In our previous studies, 21,22 the 3D structure was reported for the rst time for SrO-silicon system, however without detailed analysis. In the present study we aim to provide novel insight into structural ordering at the surface/interface that is driven by deoxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent studies, the same was achieved by the pulsed-laser deposition (PLD) method using strontium [18][19][20] and strontium oxide. 21,22 One of the key elements in epitaxial integration of functional oxides with silicon is the interface quality. However, due to the specic processing conditions, including a high temperature and an oxidizing environment, in combination with a substantial difference in the chemical properties of the materials, achieving control of the interface is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, the crystal quality of the oxide layer is limited due to the high lattice mismatch of these two buffer systems with Si. Therefore the use of more delicate buffer systems, such as metallic Sr and SrO, has been initiated, [24][25][26][27] while the mechanism of epitaxial integration of the first system with the STO layer represents the focus of this study.…”
Section: Introductionmentioning
confidence: 99%